Proceedings of the 2016 CHI Conference on Human Factors in Computing Systems 2016
DOI: 10.1145/2858036.2858055
|View full text |Cite
|
Sign up to set email alerts
|

Personal Tracking of Screen Time on Digital Devices

Abstract: Numerous studies have tracked people's everyday use of digital devices, but without consideration of how such data might be of personal interest to the user. We have developed a personal tracking application that enables users to automatically monitor their 'screen time' on mobile devices (iOS and Android) and computers (Mac and Windows). The application interface enables users to combine screen time data from multiple devices. We trialled the application for 28+ days with 21 users, collecting log data and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 43 publications
1
36
0
1
Order By: Relevance
“…Aspects of usage studied have included the times that phones are on or off [38], network activity [48], and times at which phones are in portrait or landscape mode [40]. A large amount of work concentrates on mobile app usage, including the apps people install [23], and usage patterns of app launches [9].…”
Section: Related Workmentioning
confidence: 99%
“…Aspects of usage studied have included the times that phones are on or off [38], network activity [48], and times at which phones are in portrait or landscape mode [40]. A large amount of work concentrates on mobile app usage, including the apps people install [23], and usage patterns of app launches [9].…”
Section: Related Workmentioning
confidence: 99%
“…One result from studying RQ2 was that an increased self-awareness about work and productivity does not necessarily motivate a behavior change, similar to what related work has found in the health and physical activity domain [3,22]. Hence, my goal is to extend the existing self-monitoring approach in WorkAnalytics with another persuasive strategy, goal-setting.…”
Section: Rq3: Actionable Insights To Foster Productive Behaviormentioning
confidence: 84%
“…One way to improve developers' awareness of their own behavior and foster productive behavior is to provide them with the means to self-monitor and to reflect about their actions, for example through visualizations [10,20,22]. This type of self-monitoring approach has been shown to foster behavior changes in other areas of life, such as physical activity (e.g., [5,9]) and health (e.g., [2,6]).…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the structured self-reflection allows users to self-experiment with goals and identify better behavior change strategies. There is also some research on the value of workplace self-reflection on task completion [30], [31], time management [32], [68], [69], and detachment from work [33], [34]. The research has shown that successful self-reflection approaches are often structured, since they guide users' reflection with a predefined set of questions [19], [70].…”
Section: Background: Reflective Goal-settingmentioning
confidence: 99%